Tamarind fruit extract (Tamarindus indica L.) effectively inhibits the growth of Staphylococcus aureus bacteria: Ekstrak buah asam jawa (Tamarindus indica L.) efektif menghambat pertumbuhan bakteri Staphylococcus aureus - Ni Luh Putu Sri Maryuni Adnyasari; I.G.A Dewi Haryani; Hervina; A.A.Istri Yogi Nareswari Dewi (Makassar Dental Journal, 2023)
Periodontal abscess is an infection that is located adjacent to the periodontal pockets and can cause damage to the perodontal li-gament and alveolar bone. One of the gram-positive anaerobic bacteria that play a role in abscess formation is Staphylococcus aureus, and can be inhibited by utilising tamarind fruit (Tamarindus indica L.). This study investigated tamarind fruit pulp ex-tract at concentrations of 10%, 50%, and 100% to inhibit the growth of S.aureus bacteria with true experimental in vitro with post-test only control group design. The treatment group was given 10%, 50%, and 100% tamarind fruit flesh extract. Clinda-mycin as positive control and 96% ethanol as negative control. Bacterial inhibition test on tamarind fruit pulp extract showed strong inhibition response at 10% concentration (13.05±2.21 mm, 50% (28.55±0.78 mm), and 100% (20.21±0.21 mm). It is concluded that tamarind fruit pulp extract can inhibit the growth of S.aureus bacteria.